2020
DOI: 10.1101/2020.06.26.20141176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association study of DNAJC13, UCHL1, HTRA2, GIGYF2 and EIF4G1 with Parkinson’s disease

Abstract: Rare mutations in genes originally discovered in multi-generational families have been associated with increased risk of Parkinson's Disease (PD). The involvement of rare variants in DNAJC13, UCHL1, HTRA2, GIGYF2 and EIF4G1 loci have been poorly studied or produced conflicting results across cohorts. However, they are still being often referred to as "PD-genes" and used in different models. To further elucidate the role of these five genes in PD, we fully sequenced them using molecular inversion probes in 2,40… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…2 A) [ 15 ]. The detected transport proteins also included endosomal trafficking-related proteins, such as DnaJ homolog subfamily C member 13 (DNAJC13) [ 16 , 17 ] (Fig. 2 A), which is involved in membrane trafficking through early endosomes and implicated in recycling epidermal growth factor receptor.…”
Section: Resultsmentioning
confidence: 99%
“…2 A) [ 15 ]. The detected transport proteins also included endosomal trafficking-related proteins, such as DnaJ homolog subfamily C member 13 (DNAJC13) [ 16 , 17 ] (Fig. 2 A), which is involved in membrane trafficking through early endosomes and implicated in recycling epidermal growth factor receptor.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that this variant is associated with a specific form of atypical parkinsonism, but not with typical PD. It has been shown that a number of genes previously reported as PD-associated (such as DNAJC13, UCHL1, HTRA2, GIGYF2 , and EIF4G1 ) do not play a role in PD and thus, should not be regarded as PD genes (Foo et al, 2014; Krüger et al, 2011; Lesage et al, 2010; Saini et al, 2020). Furthermore, other genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 12, 2023. ; https://doi.org /10.1101/2023.04.11.536367 doi: bioRxiv preprint revealed single nucleotide variants (SNVs) in PD-relevant genes for some LCL lines (Table 2). Amongst the idiopathic PD lines which displayed a centrosomal cohesion deficit, one line harboured a variant in the translational repressor GIGYF2, a gene at the PARK11 locus with an unconfirmed link to PD (56,57). Amongst the PD lines without a cohesion deficit, one displayed a variant in ATP13A2, and two displayed a known pathogenic missense mutation in PRKN (Table 2).…”
Section: Identification Of Gene Variants In Idiopathic Pd Samplesmentioning
confidence: 99%